Analisis Pandangan Majelis Hakim Pengadilan Agama Probolinggo Pada Putusan No. 227/Pdt.G/2024/PA.Prob Perspektif UU No.35 Tahun 2014 - Wulandari; Syafi'i, Imam; Hidayatul Hikmiyah, Hawa’ (Maqasid: Jurnal Studi Hukum Islam, 2025)
A court decision represents a concrete form of legal application by a panel of judges in resolving a case. The issue in this study lies in how the views and legal considerations of the panel of judges were formulated in rendering the decision in Case No. 227/Pdt.G/2024/PA.Prob at the Religious Court of Probolinggo. This study aims to analyze the legal basis, judicial considerations, and the consistency of the panel’s legal reasoning in the decision. The research method used is normative juridical with a case study approach, where data was obtained through document studies of the court decision and relevant literature. The results indicate that the panel of judges in this case based their considerations on the aspects of substantive justice and the principle of legal benefit for the disputing parties. Furthermore, it was found that the legal reasoning in the decision took into account a balance between legal values and societal social norms. These findings highlight the importance of consistency and clarity in formulating legal considerations so that the resulting decision can reflect a sense of justice for society.